Rigid polyurethane foams modified with thermoset polyester-glass fiber composite waste. (January 2020) - Barczewski, Mateusz; Kurańska, Maria; Sałasińska, Kamila; Michałowski, Sławomir; Prociak, Aleksander; Uram, Katarzyna; Lewandowski, Krzysztof
Abstract: This paper summarizes our work aimed at applying thermoset polyester composite waste in the preparation of polyurethane (PU) foams according to the circular economy assumptions. In the study we analyzed the influence of ground bulk moulding composites (BMC) used as a filler on the foaming process, mechanical and thermo-mechanical properties, as well as fire behavior related to structural changes of the novel recyclate-based materials. It was concluded that a modification of the reference system with BMC did not significantly affect the reactivity of the PU system, which was confirmed by observations of the dielectric polarization and temperature changes. It was found that the application of high amounts (40 wt%) of the BMC waste did not lead to any significant structural changes in the PU composite foams, which allows for a strong reduction of the price of the final product without losing its heat insulation and mechanical properties resulting from the base PU formulation. BMC-filled composite PU foams show improved thermo-mechanical stability and are characterized with higher fire resistance in comparison to unmodified PU foams. Introducing BMC into a PU system proves to be an effective way to manage such waste, creating opportunities for the preparation of a novel thermal insulating composite. Highlights: Novel approach to thermoset polyester composite waste management. Rigid polyurethane foams modified with solid waste. Strongly reduce the price of the final product without losing heat insulation and mechanical properties. Solid waste improved thermal-mechanical stability and caused higher fire resistance.